Genotypic and growing location effect on grain Î²-glucan content of barley under sub-tropical climates - Kumar, Dinesh; Narwal, Sneh; Verma, R. P. S.; Kharub, A. S. (The Indian Journal of Genetics and Plant Breeding, 2017)
Effect of genotype and growing location on barley grain beta glucan content was studied in 25 barley genotypes grown over six different locations in India. Based upon the two years results, the genotypes BCU 554, BH 963, BHS 352 and DWR 30 were having higher content of beta glucan while the genotypes Azad, BCU2030, Bilara-2, Jagriti, K 14, K 141, Lakhan, Manjula, SLOOP SA WI 3167 and SLOOP VIC VB 9953 had lower values. The growing location has also been found to affect the beta glucan content significantly. Positive simple correlation has been found between grain beta glucan content and protein, 1000 grain weight, plump kernels and test weight.